Contextos de vivência no Bairro do Cerco do Porto: cenários de pertenças, de afectividades e de simbologias - Paula Guerra (2004)
At this point, noting that the district and territory is the scene of a variety of social relationships, is a place of shared experiences, taking as reference the collective identity of the Bairro. In this context, the practices of sociability are in some way, the motive of the history of the neighborhood. The greater its magnitude depends on the existence of the neighborhood as a social environment with their own lives or simply a set of buildings and streets in an organized space. Several factors may contribute to the analysis of this district as highly relational and context of these factors is that we intend to report in this communication, evidence and logical relationships that may or may not crystallize the experience of self and hetero social exclusion.